Innovation and Transformation of Educational Supervision in the 21st Century: Analyzing the Transformation of Social Dynamics of Teachers-Students and Institutional Authority - Sumampouw, Zoya F.; Tudus, Melisa Veronika (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2025)
This study aims to analyze the transformation of educational supervision in the 21st century with a focus on the social dynamics between teachers, students, and institutional authorities. The approach used in this study is qualitative through literature studies, by reviewing various previous studies that are relevant to understanding changes in educational supervision practices. The results of the study show three main findings: first, collaboration-based supervision has a positive impact on the relationship between supervisors and teachers, and improves teaching effectiveness. Second, the integration of technology in supervision allows for more efficient and data-based supervision, although it poses challenges related to privacy. Third, the mental well-being of teachers and students is a priority in effective supervision, which has an impact on improving the overall quality of education. This study suggests that changes in the educational supervision model must prioritize collaboration, technology, and well-being to create a more inclusive and productive educational environment.